The African Bible : reading Israel's Scriptures from Africa and the African diaspora - Page, Hugh R.; Bailey, Randall C., 1947- (Minneapolis, Minn. : Fortress Press, 2010)
The Africana Bible features a critical commentary on every book of the Hebrew Bible, the Apocrypha, and Pseudepigrapha that are authoritative for many in African and African-diasporan communities worldwide. It highlights issues of concern to the global Black community (such as globalization and the colonial legacy) and the distinctive norms of interpretation in African and African Diasporan settings.
Zephaniah ? D.R. Mbuwayesango -- Haggai / K.N. Gwa -- Zechariah / J.C. Ross -- Malachi / Stacy Davis -- The Ketuvim / / Madipoane Masenya, R.S. Sadler -- Psalms / N.S. Murrell, D.T. Shannon, D.T. Adamo -- Job / Madipoane Masenya, R.S. Sadler -- Proverbs / Naomi Franklin -- Ruth / Wil Gafney -- Song of Songs / N.S. Murrell -- Ecclesiastes / J.-D. Hopkins -- Lamentations / W.A. Bailey -- Esther / D.B. Akoto -- Daniel / A.M. Mbuvi -- Ezra and Nehemiah / Herbert Marbury -- 1-2 Chronicles / R.J. Weems -- Introduction to the deuterocanonical and pseudepigraphic writings / Stacy Davis, N.S. Murrell -- 1-2 Esdras / C.L. Nash -- Tobit / Stacy Davis -- Judith / Naomi Franklin -- The Greek additions to Esther / R.C. Bailey -- Wisom of Solomon / N.S. Murrell -- Baruch / Robert Wafawanaka -- Letter of Jeremiah / V.L. Johnson -- Susanna / Stacy Davis -- Bel and the dragon / A.O. Stokes -- Prayer of Manasseh / H.R. Page Jr. -- 1-3 Maccabees / W.M. Johnson -- 4 Macca bees / E.B. Powery -- Sirach / Naomi Franklin -- Psalm 151 / Stacy Davis -- 1 Enoch / H.R. Page Jr. -- The Sybilline oracles / W.M. Johnson -- Lide of Adam and Eve / D.E. Callender Jr. -- Jubilees / J.-D. Hopkins.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc. -- Africa; Apocryphal books (Old Testament) -- Criticism, interpretation, etc. -- Africa; Black theology; Theology -- Africa